(untitled) (Global Journal of Management and Business Research, 2012)
Aim of this study was to examine the impact of viewer response profile on skepticism toward advertising and how they affect viewer response profile to skepticism toward advertising. General public was selected for this study and 170 Questionnaire were distributed out of which 150 were receiving back with response rate 88%. Findings of this study showed that viewer response profile has positive and significant impact on skepticism toward advertising. On the practical level viewer response profile and skepticism toward advertising enhance the profitability and achieve the organization goals. Newness of this study is its originality that concerns with the affect of viewer response profile on skepticism toward advertising.